2022
DOI: 10.1021/acssuschemeng.1c05800
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Optimization of a Composition-Tunable Zeotropic ORC Using LNG Cold Energy as a Heat Sink

Abstract: The organic Rankine cycle (ORC) is a promising power generation cycle to fully utilize the cold energy of liquid natural gas (LNG). ORC is usually operated under variable working conditions, and the operation performance is significantly worse than under design conditions. In this paper, a novel composition-tunable zeotropic ORC using LNG cold energybased liquid-separation condenser is proposed and a thermodynamic optimization model is formulated. A case study is then conducted to validate the superiority of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Additionally, the application of liquid-separation condensation technology has also been implemented by Sun [77], Chen [78], Pang [79], and Zhu [80] in various scenarios such as combined cooling and power cycle (CCP), LNG cold energy recovery, flash cycle, and dual cooling source system (DCS). The results all demonstrated that under specific operating conditions, the liquid-separation condenser has the capability to effectively enhance system performance.…”
Section: Liquid-separation Condensermentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the application of liquid-separation condensation technology has also been implemented by Sun [77], Chen [78], Pang [79], and Zhu [80] in various scenarios such as combined cooling and power cycle (CCP), LNG cold energy recovery, flash cycle, and dual cooling source system (DCS). The results all demonstrated that under specific operating conditions, the liquid-separation condenser has the capability to effectively enhance system performance.…”
Section: Liquid-separation Condensermentioning
confidence: 99%
“…Liquid-separation ORC coupled vapor-liquid ejector Net power output increased by 14.20% [78] ethylene/propane Liquid-separation ORC Net power output and thermal efficiency increased by 2.86% and 2.47%, respectively [79] R600a/R601a Liquid-separation organic flash cycle Condensation area decreased by 23.33% [81] R32/R236fa Liquid-separation DCS COP and dehumidification rate can reach 5.1 and 2.2 kg/h, respectively [76] R134a/R245fa Liquid-separation ORC with composition regulation Net power output increased by 4.79-9.71% [80] R32/isobutane R32/R1234ze(E) R32/R1234yf propane/isobutane propane/R1234ze(E) Liquid-separation DCS Exergy loss of evaporator decreased by 17.1-73.7% while the exergy efficiency increased by 3-59.7%; refrigerant charge decreased by 5.54-15%.…”
Section: Working Fluid Systemmentioning
confidence: 99%
“…Sung et al 22 designed a novel dual-loop ORC wherein exhaust gas and jacket cooling water acted as the heat sources. Chen et al 23 proposed a novel composition-tunable zeotropic ORC with improved power generation and cold energy utilization efficiency. Lee et al 10 developed a dual-expander organic Ranking cycle-hydrate-based desalination process that has a strong potential for electricity production.…”
Section: Introductionmentioning
confidence: 99%